Individuals with developmental prosopagnosia show independent impairments in face perception, face memory and face matching. (December 2022) - Stantić, Mirta; Pounder, Zoë; Bate, Sarah; Susilo, Tirta; Catmur, Caroline; Bird, Geoffrey
Abstract: Individuals with developmental prosopagnosia (DP) all exhibit impairments in face memory, but the specificity of these face memory impairments is debated. One problem is that standard behavioural tasks are not able to provide independent measurement of face perception, face memory, and face matching (the decision process required to judge whether two instances of a face are of the same individual or different individuals). The present study utilised a new test of face matching, the Oxford Face Matching Test (OFMT), and a novel analysis strategy to derive these independent indices. Twenty-nine individuals with DP and the same number of matched neurotypical controls completed the OFMT, the Glasgow Face Matching Test, and the Cambridge Face Memory Test. Results revealed individuals with DP exhibit impairments in face perception, face memory and face matching. Collectively, these results suggest that face processing impairments in DP are more comprehensive than has previously been suggested.